Reliability based design and analysis of earth retaining structure - Si, Thu Kyaw. (2010)
In geotechnical engineering design decisions are made under a great deal of uncertainties as, for instance, subsoil profile, in-situ engineering soil properties based on a relatively few field or laboratory tests, pore-water pressure and lateral stresses. The use of deterministic analyses and conventional safety factors can be rather deceptive and may lead the engineer into a false sense of security. In this report, analyzing and designing of semi-gravity wall first by conventional, deterministic procedures, and then subsequently extended to probabilistic analysis by generating the Hasofer-Lind reliability index corresponding to the performance function based on different modes of failures. The reliability concept adopted in this report is spreadsheet-cell-object-oriented algorithm for the first-order reliability method, FORM with correlated normal and non-normal random variables. The targeting reliability index in the range of 3-3.5 for overturning, sliding and bearing capacity failure modes are considered in designing of Semi-gravity wall. The probabilities of failure inferred from reliability indices will be compared with Monte Carlo simulations and design based on Eurocode 7. It was found that the probability of failures generated by Monte Carlo simulation were close to reliability analysis results. Furthermore, in reliability analysis, the ratio of the mean values to the design point values is similar in nature to the partial factors in Eurocode 7. This report is mainly focused on the desirable aspect of reliability-based design using the efficient and robust spreadsheet platform that is able to seek the most probable failure design point in the shortest time frame without presuming any partial factors. It also automatically reflects the sensitivities and uncertainties in the soil parameters.